Multiplicity-dependent jet modification from di-hadron correlations in pp collisions at √s = 13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Menzel, Marius; Nath, Abhishek; Pachmayer, Yvonne C.; et al. (Journal of high energy physics, 2025)
Short-range correlations between charged particles are studied via two-particle angular correlations in pp collisions at $$ \sqrt{s} $$= 13 TeV. The correlation functions are measured as a function of the relative azimuthal angle ∆φ and the pseudorapidity separation ∆η for pairs of primary charged particles within the pseudorapidity interval |η| < 0.9 and the transverse-momentum range 1 < pT < 8 GeV/c. Near-side (|∆φ| < 1.3) peak widths are extracted from a generalised Gaussian fitted over the correlations in full pseudorapidity separation (|∆η| < 1.8), while the per-trigger associated near-side yields are extracted for the short-range correlations (|∆η| < 1.3). Both are evaluated as a function of charged-particle multiplicity obtained by two different event activity estimators. The width of the near-side peak decreases with increasing multiplicity, and this trend is reproduced qualitatively by the Monte Carlo event generators PYTHIA 8, AMPT, and EPOS. However, the models overestimate the width in the low transverse-momentum region (pT < 3 GeV/c). The per-trigger associated near-side yield increases with increasing multiplicity. Although this trend is also captured qualitatively by the considered event generators, the yield is mostly overestimated by the models in the considered kinematic range. The measurement of the shape and yield of the short-range correlation peak can help us understand the interplay between jet fragmentation and event activity, quantify the narrowing trend of the near-side peak as a function of transverse momentum and multiplicity selections in pp collisions, and search for final-state jet modification in small collision systems.
Gesehen am 09.02.2026
ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Bórquez Carcamo, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, M.W. Menzel, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, F. Schlepper, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, B. Windelband, A. Yüncü, F. Zanone, B. Zhang [und 1057 weitere]